Analisis C, N, C/N Ratio Tanah dan Hasil Padi yang Diberi Pupuk Organik dan Pupuk Hayati Berbasis Azolla Pada Lahan Sawah Organik - Mieke Rochimi Setiawati; Diyan Herdiyantoro; Maya Damayani; Pujawati Suryatmana (Soilrens, 2018)
ABSTRACT Organic farming, especially organic rice requires a continuing supply of organic fertilizer in large quantity as a source of nutrition for rice plants. In long-run, organic system is can retain higher soil organic carbon (SOC), partially compensates the negative impact by improving physical and biological properties, as well as nutrient retention capacity of the soil. Azolla pinnata is an organic nitrogen source rich in protein. The high nitrogen content in A. pinnata is related to the presence of nitrogen-fixing Anabaena azollae microsimbion in A. pinnata leaves. A. pinnata compost is an alternative for biofertilizer carrier that can be used in organic rice fields. The contribution of azolla-based organic farming for organic farmers is to decrease the dependency on the animal manure in cropping season. The field experiment comprised of conventional compost as control and combination of organic fertilizer and biofertilizer with Azolla carrier. Organic fertilizer were 5 ton/hectare (ton/ha), 7.5 ton/ha, and 10 ton/ha combined with 0, 10, 20 kg/ha biofertilizer with Azolla carrier with no addition of inorganic fertilizer. Complete randomized design were used in the experiment which consisted of three replications. This technology produced organic fertilizer better than conventional compost of rice straw and manure made by farmers. Organic fertilizer base with Azolla mixture of 7.5 ton ha-1 plus solid biofertilizer (10 kg/ha) can produce 6.58 ton/ha of dry harvested grain, higher than conventional compost treatment (control). The application of organic fertilizer base on azolla and solid biofertilizers gave the increasing yield prospect of organic rice in Cisayong, Tasikmalaya regency West Java.Keywords : Azolla pinata, carbon, nitrogen, organic farming, rice.